Father Brown. Season three, part two [videorecording (DVD)] - Chesterton, G. K. (Gilbert Keith), 1874-1936 (BBC, 2016)
Welcome back to the village of Kembleford, where Father Brown uses his personal blend of intuition, psychology, compassion and justice to solve another series of gripping crimes. Assisted as always by parish secretary Mrs. McCarthy, glamorous socialite Lady Felicia Montague and her accommodating chauffeur Sid Carter, Father Brown faces threats to his town, his friends and his faith. An assassination attempt, an art heist, ritual sacrifice and murder keep the twists and turns coming.